Identifikasi Langgam Arsitektur Melayu Pada Rumah Tradisional - Yenny Novianti; Cut Azmah Fithri; Rahmad Hidayat (Universitas Syiah Kuala, 2022)
The Malay kingdom has a wide area of power. One of Malay Kingdom is Langkat Sultanate, which ruled in the North Sumatra Region, especially the Langkat Regency. Some relics of traditional Malay houses still survive as part of the traces of the Langkat Sultanate. Currently, the house of The Langkat Sultanate is still occupied and functions as a residence, but its condition is not well maintained. The existence of this architecture became a legacy of the Langkat Sultanate and is part of Malay culture. This study aims to identify the cultural style of Malay architecture, especially in the traditional house of Rumah Datuk Padang Tualang, in Tanjung Pura District, Langkat Regency. The method used is descriptive qualitative so that the description of the object in studying a phenomenon of Malay architecture can be studied more accurately and well. Studies reveal that there were changes on both the micro and macro scale. However, some elements are still maintained following the Malay Architectural style.